Growth dynamics, multiple equilibria, and local indeterminacy in an endogenous growth model of money, banking and inflation targeting - Rangan Gupta; Philton Makena (Economies, 2020)
We develop an overlapping generations monetary endogenous growth (generated by productive public expenditures) model with inflation targeting, characterized by relocation shocks for young agents, which in turn generates a role for money (even in the presence of the return-dominating physical capital) and financial intermediaries. Based on this model, we show that growth dynamics emerge with a S-shaped growth path producing three equilibria. The low and high-growth equilibria are stable, but locally indeterminate, while the medium-growth equilibrium is unstable. Since, government expenditure is productive in our model, a higher inflation-target would translate into higher growth, but under multiple equilibria, this is not necessarily always the case.
Keywords: C62; O41; O42; 330; endogenous growth; growth dynamics; inflation targeting